Toward better governance of the marine environment: an examination of the revision of China’s marine environmental protection law in 2023 - Huang, Lansong; Zhou, Rui; Wang, Quansheng (Frontiers in Marine Science, 2024)
The marine economy has become an increasingly important contributor to the global economy due to advancements in science and technology and humans' growing ability to manipulate nature.With the improvement of science and technology and the gradual enhancement of humans' ability to transform nature, the marine economy has gradually become an important growth point of the global economy. As a large marine country with a vast marine territory,, China has the important responsibility ofmission of rationally utilizing marine resources and rationally and promoting sustainable developmentgreening the development of the marine economy. Since the introduction of the Marine Environmental Protection Law of the People's Republic of China (MEPL) in 1982, China has gradually strengthened the construction of the rule of law on marine environmental protection. MEPL has undergone several revisions to improve its legal content under the guidance of national policies. On October 24, 2023, the Standing Committee of the National People's Congress revised and adopted MEPL again. This paper analyzes the changes in the contents of the new law and the legal background at home and abroad while integrating the domestic and international legal backgrounds. This paper provides an in-depth analysis of analyzes the changes made in the new law, summarizes the revision ideas, and examinesfocuses on the new law in the context of domestic and international laws. The aim is to provide a clear understanding of the spirit and purpose of the legislation.It provides an in-depth understanding of the spirit and purpose of the legislation.